The relevance of right ventricular function and dimension in patients undergoing transcatheter tricuspid edge-to-edge repair - Brunner, Stephanie; Stolz, Lukas; Kresoja, Karl-Patrik; von Stein, Jennifer; Fortmeier, Vera; Koell, Benedikt; Rottbauer, Wolfgang; Kassar, Mohammad; Goebel, Bjoern; Denti, Paolo; Achouh, Paul; Rassaf, Tienush; et al. (JACC Cardiovascular interventions, 2025)
Background - Patients with severe tricuspid regurgitation (TR) often present with abnormal right ventricular (RV) function and dimensions. - Objectives - The aim of this study was to investigate the impact of RV dysfunction and dilation on clinical outcomes in patients undergoing transcatheter tricuspid edge-to-edge repair (T-TEER). - Methods - Patients from the international EuroTR registry undergoing T-TEER between 2016 and 2023 at 20 heart valve centers across Europe were included. RV dysfunction was defined as tricuspid annular plane systolic excursion <17 mm, and RV dilation was defined as RV mid-diameter >35 mm, determined on baseline echocardiography. - Results - A total of 2,191 patients (mean age 78 ± 7 years, 53% [1,111 of 2,092] women) were analyzed. TR was successfully reduced to a severity grade of ≤2+ in 80% of patients (1,608 of 2,001). In multivariable analysis, significant predictors of mortality after T-TEER included RV dysfunction (HR: 1.05 per 1-mm tricuspid annular plane systolic excursion decrease; 95% CI: 1.03-1.08), RV dilation (HR: 1.02 per 1-mm RV mid-diameter increase; 95% CI: 1.00-1.03), and residual TR after T-TEER (HR: 1.70 for TR grade ≤2; 95% CI: 1.36-2.13). These parameters were also predictive of the combined endpoint of mortality and heart failure hospitalization. The worst prognosis was observed in patients exhibiting both RV dysfunction and dilation. - Conclusions - RV size and function, along with residual TR severity, were significant predictors of clinical outcomes, including all-cause mortality and heart failure hospitalization. Accordingly, early intervention to prevent RV dilation and dysfunction, as well as achieving maximal TR reduction, appears crucial for improving prognosis in patients undergoing T-TEER.